Re-Thinking the Value of 20th-Century Archaeological Sites in Canada - Haukaas, Colleen (Scholarship@Western, 2013)
Though archaeological sites dating to the 20th century in Ontario are eligible for protection under the recently updated Standards and Guidelines for Consulting Archaeologists, many archaeologists do not consider them to valuable heritage resources. In academic archaeology in other parts of Canada, however, 20th-century sites have proven to be useful in archaeological research in several ways. This paper will discuss how 20th-century archaeological sites are investigated in Ontario, and then compare case studies from academic archaeology in the Yukon, British Columbia, and Newfoundland and Labrador where recent archaeological sites were found to be valuable to both archaeological research and to modern descendant communities. These case studies suggest that the attitudes and practices of consultant archaeologists may not be reflective of the potential value of 20th-century archaeological sites in Ontario.